(untitled) (مجلة الواحات للبحوث والدراسات, 2015)
The purpose of this article is to attempt to apply a mathematical model in the planning of the production of the service the loan CPA in order to minimize the cost of the plan’s total production expressed in ODP goal of the model, which consists of production costs, service, labor costs and costs related to number in excess of need during periods of low demand for banking products through training as a strategy to increase the productive capacity and knowledge, especially in light of technological development at the bank and not to waste in their earnings accumulated, and according to available means, where the study concluded in the latter to propose a plan total comma included four periods of productivity and total cost estimates 3.035.072.849,97 DA. Key words: production service, product planning, model of HAX-CANDEA.